2003
DOI: 10.1590/s0036-46652003000600005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an in-house specific immunoglobulin G (IgG) avidity ELISA for distinguishing recent primary from long-term human cytomegalovirus (HCMV) infection

Abstract: SUMMARYThis article describes the standardization and evaluation of an in-house specific IgG avidity ELISA for distinguishing recent primary from long-term human cytomegalovirus (HCMV) infection. The test was standardized with the commercial kit ETI-CYTOK G Plus (Sorin Biomedica, Italy) using 8 M urea in phosphate-buffered saline to dissociate low-avidity antibodies after the antigenantibody interaction. The performance of the in-house assay was compared to that of the commercial automated VIDAS CMV IgG avidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…Other avidity cutoff values analyzed were 0.7 (Ն0.7, high avidity suggestive of past infection; Ͻ0.7, low avidity suggestive of recent infection) (1, 3); and 0.6 (Ն0.6, high avidity suggestive of past infection; Ͻ0.6, low avidity suggestive of recent infection). Cutoff values recommended by the manufacturer of Ն0.8 for high avidity, Ͻ0.8 to 0.2 for intermediate (indeterminate) avidity, and Ͻ0.2 for low avidity were not analyzed because most of the test range assigns indeterminate avidity and because the Ͻ0.2 cutoff has been shown to be too low to identify many sera from acute CMV infection (1,3,6,7,23).…”
Section: Methodsmentioning
confidence: 99%
“…Other avidity cutoff values analyzed were 0.7 (Ն0.7, high avidity suggestive of past infection; Ͻ0.7, low avidity suggestive of recent infection) (1, 3); and 0.6 (Ն0.6, high avidity suggestive of past infection; Ͻ0.6, low avidity suggestive of recent infection). Cutoff values recommended by the manufacturer of Ն0.8 for high avidity, Ͻ0.8 to 0.2 for intermediate (indeterminate) avidity, and Ͻ0.2 for low avidity were not analyzed because most of the test range assigns indeterminate avidity and because the Ͻ0.2 cutoff has been shown to be too low to identify many sera from acute CMV infection (1,3,6,7,23).…”
Section: Methodsmentioning
confidence: 99%
“…The other 3 groups modified a CMV IgG kit to include a urea buffer wash step; the Brussels and Paris groups employed 8 M urea, whereas the Stuttgart group used 6 M urea. Other investigators have taken the latter approach of modifying CMV IgG kits from different manufacturers and typically employ 6 M urea (16,17,20,22,41,42). Table 2 lists the currently available CMV IgG avidity assays known to the authors.…”
Section: Commercially Available CMV Igg Avidity Assaysmentioning
confidence: 99%
“…We concluded that the pregnant woman had thus been infected before conception. Some authors suggested that the CMV-IgG avidity assay might help distinguish primary from recurrent infection and/or exclude the risk of congenital CMV infection [ 2 ]; however, it was not used in the present case. It has been suggested that symptomatic congenital infection is rare in infants of women with preconceptional immunity.…”
Section: Discussionmentioning
confidence: 93%